The Global Financial Crisis and The Integration of Islamic Stock Markets in Developed and Developing Countries - Salina H. Kassim, (Asian Academy of Management Journal of Accounting and Finance, 2013)
This study aims to determine the impact of the 2007 global financial crisis on the integration of the Islamic stock markets. Seven Islamic stock markets are selected based on the countries’ level of development and geographical factors. The period of analysis is divided into the pre-crisis period (9 January 2005 to 22 July 2007) and the crisis period (29 July 2007 to 10 January 2010). The methodology of this study relies on the Auto- Regressive Distributed Lag approach and the multi-variate Vector Error Correction Mechanism. The 2007–2008 global financial crisis caused changes in the integration level of the Islamic stock market. Both the level of development and geographical factors are found to have a significant influence on the integration of the Islamic stock markets during the crisis and non-crisis periods. The findings have important bearings on the formulation of financial policies, in which co-integrated Islamic stock markets suggest that there is a need for policy coordination among these markets to mitigate the impacts of financial fluctuations. Financial reforms, including the reduction or removal of trade and investment barriers, will be essential if these countries are to exploit the advantages of financial interdependence.